TURBO APPLICATIONS IN THE POST BOOK LIST INDEX USING A LOT CHAIN LIST - Santi Yuliyanti; Sahni D. Purba, Skom, MM (Jurnal Sistem Informasi, 2002)
Given the index list, explanation of a word or phrase to search from a listimmediately refractive index of the book. In a chain is the most appropriate method toindex a list of books. For a list of serial dynamic data structures which are thesimplest in sequence with the pointer.